Peran Konselor dalam Mengatasi Perilaku Menyimpang Remaja di Sentra Paramita Mataram - Emha Zainul Mukminin; T. Tri Panca Arbiansyah; H. Yahya (Ulul Albab: Journal Da`wah and Social Religiosity, 2024)
Adolescence is a period of self-discovery, typically ranging from ages 12 to 20. It is a transitional phase, meaning it does not entirely break with or change what happened before, but rather represents a shift from one stage. Adolescence is a time of change, where physical changes are closely linked to shifts in attitudes and behaviors. In general, changes during adolescence include an increased sense of ego, a growing sense of responsibility for oneself, and a heightened awareness of personal challenges. Adolescence can also be a problematic period, as teenagers, feeling independent, often try to solve their own problems. This study aims to explore the role of counselors in addressing deviant behavior among adolescents at the Balai Sentral Paramita Mataram. The research method used was a descriptive qualitative approach, involving in-depth interviews with counselors, social workers, and adolescents being mentor at Balai Sentra Paramita Mataram. The findings revealed five types of deviant behavior among the adolescents: theft, substance abuse, possession of sharp weapons, sexual assault, and other deviant behaviors.The study concludes that the role of community and Balai Sentral Paramita Mataram is crucial in helping to rehabilitate these adolescents. Since they cannot be prosecuted under the law, it is important to provide them with proper guidance so that they do not repeat their deviant actions. Some adolescents are sent to the Balai because their parents are unable to educate them properly, and the Balai serves as a place for character building and rehabilitation.